International Drying Symposium IDS2000, 28-31 August 2000, The Netherlands - International Drying Symposium IDS2000 2000 : Noordwijkerhout, The Netherlands); Kerkhof, P.J.A.M.; Coumans, W.J.; Mooiweer, G.D. (Netherlands : Elsevier Science B.V., 2000)
The Dutch working party on drying has taken the responsibility for organizing the 12th International Drying Symposium (IDS2000), the world's foremost event in the field of solids drying
Editors, P.J.A.M. Kerkhof, W. J. Coumans, G. D. Mooiweer
System requirements : this CD-ROM can be used on any PC or Macintosh computer with a CD-ROM drive that has a recent version of a web browser, such as Netscape or Microsoft Internet Explorer, installed
Keywords: Science -- Netherlands